Comparative Genomics of Four Isosphaeraceae Planctomycetes: A Common Pool of Plasmids and Glycoside Hydrolase Genes Shared by Paludisphaera borealis PX4T, Isosphaera pallida IS1BT, Singulisphaera acidiphila DSM 18658T, and Strain SH-PL62 - Ivanova, Anastasia A.; Naumoff, Daniil G.; Miroshnikov, Kirill K.; Liesack, Werner; Dedysh, Svetlana N. (Frontiers in Microbiology, 2017)
The family Isosphaeraceae accommodates stalk-free planctomycetes with spherical cells, which can be assembled in short chains, long filaments, or aggregates. These bacteria inhabit a wide variety of terrestrial environments, among those the recently described Paludisphaera borealis PX4T that was isolated from acidic boreal wetlands. Here, we analyzed its finished genome in comparison to those of three other members of the Isosphaeraceae: Isosphaera pallida IS1BT, Singulisphaera acidiphila DSM 18658T, and the uncharacterized planctomycete strain SH-PL62. The complete genome of Paludisphaera borealis PX4T consists of a 7.5 Mb chromosome and two plasmids, 112 and 43 kb in size. Annotation of the genome sequence revealed 5802 potential protein-coding genes of which 2775 could be functionally assigned. The genes encoding metabolic pathways common for chemo-organotrophic bacteria, such as glycolysis, citrate cycle, pentose-phosphate pathway, and oxidative phosphorylation were identified. Several genes involved in the synthesis of peptidoglycan as well as N-methylated ornithine lipids were present in the genome of P. borealis PX4T. A total of 26 giant genes with a size > 5 kb were detected. The genome encodes a wide repertoire of carbohydrate-active enzymes (CAZymes) including 44 glycoside hydrolases (GH) and 83 glycosyltransferases (GT) affiliated with 21 and 13 CAZy families, respectively. The most-represented families are GH5, GH13, GH57, GT2, GT4, and GT83. The experimentally determined carbohydrate utilization pattern agrees well with the genome-predicted capabilities. The CAZyme repertoire in P. borealis PX4T is highly similar to that in the uncharacterized planctomycete SH-PL62 and S. acidiphila DSM 18658T, but different to that in the thermophile Isosphaera pallida IS1BT. The latter strain has a strongly reduced CAZyme content. In P. borealis PX4T, many of its CAZyme genes are organized in clusters. Contrary to most other members of the order Planctomycetales, all four analyzed Isosphaeraceae planctomycetes have plasmids in numbers varying from one to four. The plasmids from P. borealis PX4T display synteny to plasmids from other family members, providing evidence for their common evolutionary origin.